Why Is the Depletion of Our Important Fish Stocks so Persistent? - Wilson, James (Maine Policy Review, 2023)
In the 1980s and 1990s, two events changed the fundamental structure of Maine's coastal ecology: inshore herring and then nearshore groundfish stocks were overfished and disappeared. Surprisingly, even without fishing, there has been no recovery. Standard fisheries management assumes that the recovery of any locally overfished place should be quick – fish from other places will 'fill in.' In contrast, recent scientific work on social learning among animals suggests that fish have communication and learning abilities comparable to other vertebrates. Learning allows groups of fish to adapt to much more local places than possible if adaptation depended on genetics alone. In these circumstances, the reason local depletions are so persistent may be because we preferentially harvest older fish that are the source of the learned experience required for continuing local adaptation. The important lesson for Maine is that sustainability will require more active local management.
Keywords: fisheries; social learning; local adaptation; learned recruitment; multi-scale; complex system; persistent depletion; social ecological systems